INSTITUTIONAL INVESTORS, CONSUMER SENTIMENT AND SUSTAINABILITY PERFORMANCE MODERATED BY GREEN INNOVATION - Fenny Marietza; Nila Aprila; Madani Hatta (Bajang Institute, 2023)
This study aims to examine the effect between institutional ownership and consumer sentiment using CCI index on sustainability performance moderated by green innovation. The sustainability performance measured by ESG index, and the green innovation variable with two indicator such as green product and green process is a variable that has never been used before as a moderation variable. The sample of this study is companies listed on the LQ45 Index on the IDX from 2018 to 2021. The analysis method used is moderation regression analysis assisted by EViews in data processing. The results show institutional ownership has no influence on the company's sustainability performance. The consumer sentiment has a positive influence on the company's sustainability performance. Meanwhile, green innovation cannot be a variable that can strengthen or weaken the influence of institutional ownership and consumer sentiment on sustainability performance.